Developing a method for diagnosing the level of the Kirov Region social and economic development within the Volga Federal District of the Russian Federation - R. S. Golovnin; T. V. Baibakova (Вестник университета)
The authors have set the task to assess the socio-economic development level of the Kirov Region. The Volga Federal District has been chosen as the base of comparison. The key problems of the Russian constituent entities territorial development have been analyzed, and the authors’ methods of characterizing the regional social and economic development level published in early scientific works studied. The order of calculating normative values for selected indicators used to assess the Volga Federal District regions has been given. The diagnostic procedure has been carried out to characterize the Kirov Region social and economic development level in comparison with other district entities in the context of the economic development pace and the regional development overall level. Based on the analysis, the initial hypothesis of the study has been confirmed, and conclusions drawn about the general lag of the region from the federal district, while higher rates of its development in comparison with other regions of the Volga Federal District noted. The study results application scope consists in its further use within the framework of scientific works on asses–sing economic development of other district entities, as well as the used methodology application for other entities. The conclusion formulates further direction for improving the diagnostics of the Kirov Region social and economic development level and names specific steps to detail and clarify the future study results.